2003
DOI: 10.1007/s00421-002-0722-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the menstrual cycle on performance of intermittent, high-intensity shuttle running in a hot environment

Abstract: The present study examined the impact of the menstrual cycle and oral contraceptive use on performance of high intensity intermittent running in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 32 publications
3
56
3
Order By: Relevance
“…Investigations into muscle contractile strength during the cycle have produced conflicting results, however, when methodological shortcomings are addressed it appears that fluctuations in female steroid hormones do not affect muscle strength and fatigability [73]. Limited soccer-specific research exists but one study showed no performance differences in high-intensity intermittent shuttle running throughout the menstrual cycle [91], although differences in core temperature were not found in this study which may explain these findings. At present there are a number of conflicting reports within the literature, methodological concerns and a lack of specificity to team sports, specifically soccer activity.…”
Section: 1)contrasting
confidence: 61%
“…Investigations into muscle contractile strength during the cycle have produced conflicting results, however, when methodological shortcomings are addressed it appears that fluctuations in female steroid hormones do not affect muscle strength and fatigability [73]. Limited soccer-specific research exists but one study showed no performance differences in high-intensity intermittent shuttle running throughout the menstrual cycle [91], although differences in core temperature were not found in this study which may explain these findings. At present there are a number of conflicting reports within the literature, methodological concerns and a lack of specificity to team sports, specifically soccer activity.…”
Section: 1)contrasting
confidence: 61%
“…Two other studies have examined intermittent activity (Lynch and Nimmo 1998;Sunderland and Nevill 2003). Unlike the present study, neither found a significant difference in performance between menstrual phases.…”
Section: Discussioncontrasting
confidence: 83%
“…al 2001). Sunderland and Nevill (2003), required participants to complete 20 m intervals of varying speed for repeats of 15 min until exhaustion. Although some of the intervals were maximal sprints, others were walk, jog ($55%), or cruising $ 95% _ V O 2 max À Á speed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, recent studies are finding that the physiological variables velocity at V _ O 2max (vV _ O 2max ) and peak treadmill velocity (PTV) may be more highly predictive of endurance running performance than variables such as V _ O 2 max and blood lactate (Billat et al 2003;Noakes et al 1990). However, many studies have focused solely on the physiological variables of V _ O 2max , blood lactate and submaximal and maximal heart rate (Giacomoni et al 2000;Marsh and Jenkins 2002;Sunderland and Nevill 2003). No one study has as yet focused on these more recent variables suggested to be important predictors of performance.…”
Section: Introductionmentioning
confidence: 97%